Molecular dynamics for computational proteomics of methylated histone H3 - Grauffel, Cédric; Stote, Roland H.; Dejaegere, Annick (Biochimica et biophysica acta, 2015)
Post-translational modifications of histones, and in particular of their disordered N-terminal tails, play a major role in epigenetic regulation. The identification of proteins and proteic domains that specifically bind modified histones is therefore of paramount importance to understand the molecular mechanisms of epigenetics. We performed an energetic analysis using the MM/PBSA method in order to study known complexes between methylated histone H3 and effector domains of the PHD family. We then developed a simple molecular dynamics based predictive model based on our analysis. We present a thorough validation of our procedure, followed by the computational predictions of new PHD domains specific for binding histone H3 methylated on lysine 4 (K4). PHD domains recognize methylated K4 on histone H3 in the context of a linear interaction motif (LIM) formed by the first four amino acids of histone H3 as opposed to recognition of a single methylated site. PHD domains with different sequences find chemically equivalent solutions for stabilizing the histone LIM and these can be identified from energetic analysis. This analysis, in turn, allows for the identification of new PHD domains that bind methylated H3K4 using information that cannot be retrieved from sequence comparison alone. Molecular dynamics simulations can be used to devise computational proteomics protocols that are both easy to implement and interpret, and that yield reliable predictions that compare favorably to and complement experimental proteomics methods. This article is part of a Special Issue entitled Recent developments of molecular dynamics. [Display omitted] •We analyzed complexes of methylated histones and PHD domains by molecular dynamics.•We devised a computational proteomics protocol for predicting new histone binders.•We present a thorough validation of the procedure.•We identify new PHD domains that bind methylated histone H3.•Competitive proteomics tools can be based on molecular dynamics simulations.